Inovasi Pengembangan Metode Pembelajaran dengan Menggunakan Real Avatar-Based Learning dalam Pendidikan Keperawatan: A Bridge Connection Theory and Practice di STIKEP PPNI Jawa Barat - Purnama, Heni; Dharmansyah, Dhika; Calisane, Nyanyu Nina Putri; Lindayani, Linlin (Jurnal Keperawatan Soedirman, 2017)
Virtual learning is one of the most effective and efficient learning methods, especially in improving skills including soft skills. In Indonesia, the problem-based learning methodology (PBL) is the most widely applied but has weaknesses in helping to bridge the students in the application of theory to practice. The purpose of this research was to develop learning method by using avatar-based learning to self-directed learning, which is one of the main competencies of nursing education that is lifelong learning. This study was quasi experiment with one group of intervention. Respondents in this study were nursing students of stratum 1 level four. The Self-Directed Learning Instrument (SDLI) was used to measure this research outcome. The paired t-test was used to evaluate the effectiveness of this method against outcomes. A total of 40 students agreed to participate in the study. Before intervention, the mean score for the total self-directed learning score was 72.3 (SD = 8.97). Based on the results of paired t-test about the effectiveness of real-avatar-based learning on self-directed learning, was found that after applied real-avatar based-learning for Medical Surgical Nursing III course there were an increasing of the self-directed learning (different value = 4.56, p value = 0.001). Learning method by applying real avatar-based learning was effective in improve student’s self-directed learning especially on the aspect of improvement of planning, implementation and self-monitoring. For further research, using more rigors with other outcomes is needed to reinforce the effectiveness of this method.